2016
DOI: 10.3141/2568-15
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Property Accessibility and Neighborhood Built Environment on Single-Unit and Multiunit Residential Property Values

Abstract: Recent consumer surveys and empirical studies suggest linkages between property accessibility, neighborhood built environment, and residential property values. This paper describes a comprehensive study that was undertaken to understand the impacts of property accessibility, neighborhood built environment, and other contributing factors on single-unit and multiunit residential property values. The study used a sample of more than 4,500 single-unit and 2,300 multiunit residential properties collected in more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 30 publications
(46 reference statements)
0
7
0
4
Order By: Relevance
“…Cervero (2002) found that land-use diversity at origin and destination lowered the chance of private-vehicle usage, compared with public transport usage. Guo [13,14] used land-use mix and net residential density as factors to quantify the walkable environment.…”
Section: Case Context and Data Inputsmentioning
confidence: 99%
“…Cervero (2002) found that land-use diversity at origin and destination lowered the chance of private-vehicle usage, compared with public transport usage. Guo [13,14] used land-use mix and net residential density as factors to quantify the walkable environment.…”
Section: Case Context and Data Inputsmentioning
confidence: 99%
“…Previous studies in the transportation domain (e.g., Christoforou et al 2010 ; Zhang et al 2014 ; Guo and Peeta 2015 ; Guo et al 2016a , b ) have utilized random parameters models to capture the unobserved heterogeneity present in the data. Fixing the parameters to be constant when they vary across observations can lead to inconsistent, inefficient, and biased parameter estimates (Washington et al 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Only automobile travel was included in this study. Additional studies are needed to understand the impacts of internal curing of bridge decks on freight carriers (29), traffic flows (30), pedestrians (31), bicycle users (32), built environment (33), and accessibility (34). In both the partial closure and full closure alternatives, the length of the work zone included the length of the bridge and the length of the approaches on both sides because the work zone must be longer to provide potential detour options to users before they reach the work zone.…”
Section: Case Studymentioning
confidence: 99%